The perception and differences between organic and conventional management practices on yield and profitability of paddy in Ledang Johor / Siti Nuratikka Ramli - Ramli, Siti Nuratikka (Faculty of Plantation and Agrotechnology, 2016)
The purpose of this study is about the perception and differences between organic and conventional management practices on yield and profitability of paddy. The objective was to obtain farmers perception between organic and conventional management and to compare the yield and profitability between organic and conventional for paddy fields. This study applied the survey study where questionnaire distributed to the selected location of study. This study was conducted among the farmers in Ledang, Johor and the population of the farmers is about 48 respondents for organic management and 71 respondents for conventional management. By using the questionnaire, the data and information was collected and analyzed. The result for reliability statistics for organic management is .612 and .646 for conventional management. It means both data is accepted. After that, for The Pearson's Correlation for organic management between independent variable and dependent variable do not have significant because environment, knowledge and income have no effect on yield. For the conventional management there are significant differences between independent variable and dependent variable such as between knowledge and yield (r=-.237, p<O.05) and for environment and income there is no significant on yield. The regression for conventional management, there is significant difference with p<O.05 indicated that the knowledge factor is dominant factor contribute towards yield of paddy and percentage R2 show 5.6% because the questionnaire is not good to quite the fit data. Based on T-Test result, comparison shows that there is significant difference of yield between organic and conventional management p<O.01. Meanwhile, there is no significant difference of profitability between organic and conventional management respectively. It can be concluded that yield and profitability of organic management and conventional management have differences because conventional paddy get highest yield.